Mierle Ukeles, maintenance art and the commodity counter-spell - Pereira, Ricardo Cabral (Farol, 2025)
This article presents the works *I Make Maintenance Art One Hour Everyday* and *Touch Sanitation*, by performance artist Mierle Laderman Ukeles. Drawing on contributions from the recent interdisciplinary field of discard studies, I observe that public-private urban cleaning systems have invented for waste the fiction of an impossible "outside," which choreographs the movement of goods, people, machines, and animals through the city. In this sense, and thinking with Ursula Le Guin, I propose Ukeles’ maintenance art as a bag of maintenance stories, a counter-spell of the commodity, opening spaces of visibility in the field of arts against the forgetting of throwing away.